Regulating the Future: The AI Act, EU Principles, and the Challenge of Member State Equality - Oręziak, Bartłomiej (Unequal Equals? The Status of Member States in an Integrating European Union, 2026)
This chapter analyses the legal regulations regarding artificial intelligence (AI) adopted within the EU. The primary objective is to highlight the benefits and costs borne by EU Member States as they adapt to an increasingly unified EU legal system. The analysis examines AI-related EU secondary law through the lens of the legal principles of the EU’s primary law, focusing on the principles of conferral, subsidiarity, proportionality and equality. The chapter investigates the compatibility of the newly adopted AI Act with the overarching legal principles, particularly the considerations concerning its legal basis in EU primary law. Hence, the conclusions are presented based on linguistic, systemic and teleological interpretations. The concluding section is divided into two segments. The first presents the core insights derived from the analysis, without reiterating each finding. The second offers observations on how the EU should approach AI regulation to ensure adherence to the equality principle among the Member States.